(untitled) (Research, Society and Development, 2021)
Women’s health is a process full of factors and phases. One of the most important and frequent problems is cervix cancer, that should be tracked in all life periods, including pregnancy. Objectives: As general, we have: address the importance of the pap smear procedure in pregnant women. As for the specific ones, they are: describe the cellular types observed in pregnancy samples, correlating them to the hormonal action from the phase and connecting it to the most commonly found microorganisms in the results of expecting women. Methodology: Systematic literature review, with a total of 39 selected materials, including scientific papers, guideline manuals or websites from cancer research institutes – most of these obtained from scientific databases and considered within the last completed 3 years, in Portuguese and English. Results and Discussion: The factors that contribute to the rates of acceptance of the procedure were discussed, as well as the levels of importance and safety around pap smear, independently of gestation period. Conclusion: The pap smear is a trustworthy process for pregnant women, and having it done is directly related to the levels of sexual education and access of healthcare services, being then able to significantly increase the women’s health around the country.